VALIDAÇÃO DE MODELOS DE AFILAMENTO PARA ESTIMATIVA DO DIÂMETRO, ALTURA E VOLUME EM POVOAMENTO COMERCIAL DE EUCALIPTO - LEAL, Fabrício Assis; CASTRO, Renato Vinícius Oliveira; MATRICARDI, Eraldo Aparecido Trondoli (Brazilian Journal of Biometrics, 2017)
This study aimed to evaluate the performance of not segmented taper functions validation of the estimated diameter, height and volume of Eucalyptus urophylla S. T. Blake, commercial plantations located in the region of Rio Verde, GO. A total of 98 trees were random selected and rigorously scaled. From the 98 trees, 60 were used to fit the models, and 38 were used for validation. The estimated diameter, height and total volume had excellent fits, but when the evaluation involved volume per section, the deviations were higher in all models. After the analysis it was found that the Demaerschalk’s model was the most stable among all tested models, including those of the validation process.